Effect of o-Cresol, Resorcinol and Hydroquinone on Citric Acid Productivity by Aspergillus niger in Stirred Fermentor - SITKI ÇEVRIMLI*, BEKIR; YASAR†, AHMET; KARIPTAS‡, ERGIN (Asian Journal of Chemistry, 2009)
Effects of o-cresol, resorcinol and hydroquinone, which are toxic chemicals, on citric acid biosynthesis and biomass in the artificial culture setting of Aspergillus niger using batch fermenter are examined in the most favourable fermentation conditions and a model is proposed. According to this model, maximum citric acid concentration is 48.3 g L-1 in a culture that does not contain any toxic chemicals, whereas the maximum concentrations obtained in cultures containing 15 mg L-1 o-cresol, 45 mg L-1 resorcinol and 35 mg L-1 hydroquinone are 86.7, 82.8 and 86.8 g L-1, respectively. Moreover, addition of toxic chemicals to the culture reduces fermentation time by 24 h.